Research on the establishment of evaluation index system of the aging construction of the community - Li, Kun; Mei, Wen-Bing; Huang, Yi-Zhe (Frontiers in Public Health, 2023)
Introduction Constructing the evaluation index system for the community's aging-friendly construction can provide a decision-making basis for the overall investment and priority satisfaction strategy for the community's aging-friendly construction. Methods Through questionnaire survey and statistical analysis, this paper evaluates and analyzes the satisfaction level of various indicators of the community's aging-friendly construction. Results The results show that the community's humanistic care, public environment, and socio-economic criteria are significantly linearly linked to the overall construction satisfaction level. There are significant differences in the general satisfaction level of older adults in the variables of “age, educational background, residence duration, residence personnel, number of children, and marital status”. Discussion To this end, the article concludes with specific recommendations that improving older-adult care services for older adults with low age and high education, helping older adults in the community to familiarize themselves with the community environment as soon as possible, cultivating the professional abilities of community service personnel, reflecting the warmth of the community for older-adult care and improving social security capabilities are the core content of the future community building for aging.